2020
DOI: 10.1155/2020/7506590
|View full text |Cite
|
Sign up to set email alerts
|

Current Progress on Assessing the Prognosis for Anti-N-Methyl-D-Aspartate Receptor (NMDAR) Encephalitis

Abstract: Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis is the most common antineuronal antibody encephalitis in autoimmune encephalitis found at present. It has complex clinical manifestations such as psychiatric and behavioral abnormalities, seizures, movement disorders, consciousness, and autonomic dysfunction. The relationship between those manifestations and prognosis is unclear. Electroencephalography (EEG) is gradually becoming useful in the evaluation of the prognosis of anti-NMDAR encephalitis patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 63 publications
0
22
0
6
Order By: Relevance
“…However, only 8.39% of the patients in our cohort had a tumor, with ovarian teratoma comprising 84.2% of the tumors diagnosed in females. Other studies of Chinese or Asian cohorts have also reported a relatively low prevalence of tumors ( Supplementary Table 4 ) [Lim et al ( 24 ), 22.7%; Wang et al ( 25 ), 8%; Liu et al ( 22 ), 6.7%; Zhang et al ( 26 ), 8.1%]. The heterogeneity among Asian and Western populations might be due to different genetic backgrounds and epidemiologic factors.…”
Section: Discussionmentioning
confidence: 85%
“…However, only 8.39% of the patients in our cohort had a tumor, with ovarian teratoma comprising 84.2% of the tumors diagnosed in females. Other studies of Chinese or Asian cohorts have also reported a relatively low prevalence of tumors ( Supplementary Table 4 ) [Lim et al ( 24 ), 22.7%; Wang et al ( 25 ), 8%; Liu et al ( 22 ), 6.7%; Zhang et al ( 26 ), 8.1%]. The heterogeneity among Asian and Western populations might be due to different genetic backgrounds and epidemiologic factors.…”
Section: Discussionmentioning
confidence: 85%
“…18 F-FDG PET has also been shown to be superior to morphological imaging in the early diagnosis of autoimmune encephalitis 15 . The increasing number of publications studying the results of brain 18 F-FDG PET in autoimmune encephalitis over the past decade is in dire need of consolidation [13][14][15][16][17][18][19][20][21][22][23][24] . The literature is saturated with isolated case-reports and retrospective studies conducted on a small number of patients, leaving the role of PET in the initial assessment of the disease unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The second clinical implication in this case is that her symptoms improved after oral administration of MTX. At the acute stage, she was treated with first-line (glucocorticoid, IVIG, and PE) and second-line treatments (cyclophosphamide) for anti-NMDAR encephalitis [ 9 , 10 , 11 ]. However, because she did not respond to these treatments and anti-NMDAR antibodies in CSF remained positive, we started oral administration of MTX.…”
Section: Discussion/conclusionmentioning
confidence: 99%